Penyuluhan Stunting Pada Ibu Hamil Di Desa Pungka Kecamatan Unte Iwes Kabupatan Sumbawa - hamdin, Hamdin; Abdul Hamid; Herni Hasifah (Pusat Riset dan Inovasi Nasional, 2024)
Stunting describes chronic malnutrition during growth and development from early life. This situation is presented with a height-for-age (TB/U) z-score value of less than -2 standard deviations (SD) based on WHO growth standards. This service aims to provide understanding to the community about stunting. The results of community service that has been carried out in Pungka village, Unter Iwes sub-district with assistance to pregnant women in preventing stunting through socialization is the right way to provide information about preventing stunting to pregnant women and the community in general. better understand and apply ways to prevent stunting and start adopting the habit of providing nutritious food and clean and healthy living habits. The conclusion of this counseling was that several things were conveyed, namely awareness of the importance of health and the importance of development from the beginning of a mother's pregnancy to the child's growth and development to prevent the golden generation from occurring in a condition or problem called stunting